Consumption and Retail in Urban Spaces: Studies on Italy and Catalonia - Rosario Sommella (Bollettino della Società Geografica Italiana)
The article, based on the scientific results of the last phase of the project “Retail, Consumption, and the City: Practices, Planning and Governance for Urban Inclusion, Resilience and Sustainability”, proposes further reflections on the changing urban landscapes of retail and consumption through studies on Italy and Catalonia. This stage of the research project has been aimed at investigating – through specific in-depth studies (thematic or related to case studies) – aspects not adequately dealt with in the published volumes of the seven research units, or even to take inspiration from themes and cases already dealt with to advance in a reflection that could contribute to build a further piece of a new research agenda on retail, consumption, and the city. By cross-referencing descriptive evidence and theoretical reflections, the article traces the main themes of this special issue, with regard to the evolutionary and, in some cases, analytical trajectories starting as from the different case studies analyzed, all aimed at reflecting on the relationship between consumption, retail and urban spaces in Italy and Catalonia at different scales.